The recovery of muscle function and glycogen levels following game-play in young elite male ice hockey players - Thorsteinsson, H.; Vigh-Larsen, J. F.; Panduro, J.; Fristrup, B.; Kruse, D. Z.; Gliemann, L.; Egeland, M.; Olesen, J. L.; Aagaard, P.; Randers, M. B.; Krustrup, P.; Nybo, L.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Despite the frequent occurrence of congested game fixtures in elite ice hockey, the postgame recovery pattern has not previously been investigated. The purpose of the present study was therefore to evaluate the acute decrements and subsequent recovery of skeletal muscle glycogen levels, muscle function and repeated-sprint ability following ice hockey game-play. Sixteen male players from the Danish U20 national team completed a training game with muscle biopsies obtained before, postgame and following ~38 h of recovery (day 2). On-ice repeated-sprint ability and muscle function (maximal voluntary isometric [MVIC] and electrically induced low- (20 Hz) and high-frequency (50 Hz) knee-extensor contractions) were assessed at the same time points, as well as ~20 h into recovery (day 1). Muscle glycogen decreased 31% (p < 0.001) postgame and had returned to pregame levels on day 2. MVIC dropped 11%, whereas 50 and 20 Hz torque dropped 21% and 29% postgame, respectively, inducing a 10% reduction in the 20/50 Hz torque ratio indicative of low-frequency force depression (all p < 0.001). While MVIC torque returned to baseline on day 1, 20 and 50 Hz torque remained depressed by 9%-11% (p = 0.010-0.040), hence restoring the pre-exercise 20/50 Hz ratio. Repeated-sprint ability was only marginally reduced by 1% postgame (p = 0.041) and fully recovered on day 1. In conclusion, an elite youth ice hockey game induces substantial reductions in muscle glycogen content and muscle function, but only minor reductions in repeated-sprint ability and with complete recovery of all parameters within 1-2 days postgame.